2021
DOI: 10.1002/fsn3.2335
|View full text |Cite
|
Sign up to set email alerts
|

Pea protein isolate characteristics modulate functional properties of pea protein–cranberry polyphenol particles

Abstract: Plant polyphenols have a natural binding affinity for proteins, and their interaction can be exploited to form diverse aggregate particles. Protein–polyphenol particles utilized as food ingredients allow consumers to incorporate more health‐benefiting plant bioactives into their diets. The functional properties of the protein–polyphenol particles can be influenced by many factors, including complexation conditions and starting material properties. Here, cranberry polyphenols extracted from pomace were complexe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…Polyphenols naturally bind to proteins to form insoluble, stable colloidal protein-polyphenol particles, which when used as food ingredients provide more health benefits to consumers from additional bioactives [ 99 ]. Strauch and Lila [ 99 ] examined the effect of protein processing on the physiochemical properties of the pea protein-cranberry polyphenol system and found that chemical differences between proteins affected polyphenol binding and influenced digestibility. It was demonstrated that solubility was affected by both the process of forming particles and the protein-cranberry polyphenol binding [ 99 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Polyphenols naturally bind to proteins to form insoluble, stable colloidal protein-polyphenol particles, which when used as food ingredients provide more health benefits to consumers from additional bioactives [ 99 ]. Strauch and Lila [ 99 ] examined the effect of protein processing on the physiochemical properties of the pea protein-cranberry polyphenol system and found that chemical differences between proteins affected polyphenol binding and influenced digestibility. It was demonstrated that solubility was affected by both the process of forming particles and the protein-cranberry polyphenol binding [ 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…Strauch and Lila [ 99 ] examined the effect of protein processing on the physiochemical properties of the pea protein-cranberry polyphenol system and found that chemical differences between proteins affected polyphenol binding and influenced digestibility. It was demonstrated that solubility was affected by both the process of forming particles and the protein-cranberry polyphenol binding [ 99 ]. Since it has been determined that the functional properties of the protein-cranberry polyphenol particles are impacted by the properties of the protein isolate raw material, more studies need to be performed on the selection of protein isolate starting material for the desirable functional food [ 99 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forming protein complexes with other proteins or other compounds can be an unintended consequence of combining materials in one matrix or can be intentionally induced to achieve certain functions, such as colon-targeted drug delivery [ 80 ] or to confer an added nutritional benefit [ 81 ].…”
Section: Crosslinking Complexation and Other Modificationsmentioning
confidence: 99%
“…In contrast to the positive effects of anthocyanins and hydroxycinnamic acids, protein–polyphenol complexes reduce the digestibility of pea and soybean PI. Nine commercial pea PI with different physical and chemical characteristics were used to form complexes with polyphenols from cranberry pomace [ 81 ]. For some PI, no significant differences were found in the pepsin digestion of non-complexed and complexed proteins; however, all complexed isolates were less extensively hydrolysed by pancreatin digestion.…”
Section: Crosslinking Complexation and Other Modificationsmentioning
confidence: 99%